Registros vocais no canto: aspectos perceptivos, acústicos, aerodinâmicos e fisiológicos da voz modal e da voz de falsete - Salomão, Gláucia Laís (2008)
The purpose of this study was to investigate the relationship between the production and the perception of the modal and falsetto s registers in tones sang by male choir singers.104 tones were analyzed, 52 sand in modal register, 52 sang in falsetto register. The data for the analyses of the vocal registers production were obtained by means of inverse filtering of the sound irradiated from the mouth and by means of the electroglottography. The following measures were extracted: Fundamental Frequency (F0), duration of the Closed Phase, Maximum Flow Declination Rate, and Amplitude of the Alternating Current. Also, the following measures were calculated: Closed Quotient, Normalized Amplitude Quotient and level difference between the two lowest partials in the glottal source spectrum (H1 H2). The results showed clear differences between the modal and the falsetto registers. The values found for the Closed Quotient, the Maximum Flow Declination Rate and the Alternating Current Amplitude were predominantly greater in the modal than in the falsetto register. The Maximum Flow Declination Rate and H1 H2 values, on the other hand, were greater in the falsetto register than in the modal. The correlation analysis of the acoustical parameters showed a clear covariation between the Closed Quotient, the H1 H2 values, the Normalized Amplitude Quotient and Maximum Flow Declination Rate. The data for the analyses of the vocal registers perception were obtained from a forced choice test. The number of votes for modal was compared with the voice source parameters values. The results showed that tones with high values of Closed Quotient and low values of H1 H2 and of Normalized Quotient Amplitude were typically associated with higher number of votes to the modal register, and vice-versa. Our results suggest that the acoustic manifestations of the phonatory dimension related to the vocal registers are gradient and its perceived characteristics are as much distinct as they are wider apart in the continuous